Novel type-2 fuzzy logic technique for handover problems in a heterogeneous network. Issue 9 (2nd September 2018) - Saeed, Mohamed; Kamal, Hanan; El-Ghoneimy, Mona
ABSTRACT: Small cells are deployed in the long-term evolution—advanced (LTE-A) data standard to satisfy rapidly increasing data rates at hotspots and enhance coverage in buildings. Small cells are low-cost, low-power nodes with limited coverage. With small cells, the more sophisticated network architecture increases the difficulty of dealing with mobility management. The conflict between traffic demands and network resources is also very important, and the signalling overhead (ping-pong) in the handover procedure should be considered in mobility management. With the aim of solving these issues, efficient handover algorithms are being used to enhance mobility management in small-cell networks. This article presents a new handover optimization algorithm for LTE-A networks based on fuzzy logic. It consists of selecting the optimum handover margins for both macro and small cells which are required for the handover process to optimize the performance metrics. The proposed handover optimization technique is evaluated and compared with two well-known handover algorithms. The results show that it achieves a minimum call drop rate and has a minimum number of handovers.